"Playing school": Creating possibilities to inspire future Black male teachers through culturally relevant play. Issue 2 (11th June 2018) - Bryan, Nathaniel; Jett, Christopher C.
Abstract : Purpose: Much of the extant research literature on the initiatives to attract, inspire and recruit Black males to the teaching profession has focused on middle and high school students. Black boys' socialization into dominant narratives regarding who can and cannot become teachers occurs as early as in early childhood classrooms; however, little attention has been given to ways to attract, inspire and recruit them to the professional teaching ranks where a paltry 2 per cent are Black men. Design/methodology/approach: This paper explores the concept of imaginative play experiences with respect to Black boys and unearths possibilities for future Black male teachers through culturally relevant play. Findings: Based on findings from the literature, this conceptual paper makes connections between the early childhood play literature and the Black male teacher recruitment and retention literature to create possibilities to inspire Black boys to enter the teaching profession. Originality/value: This paper presents a nuanced integration of imaginative play and culturally relevant pedagogy with specific attention to Black males.